RANCANG BANGUN ALAT MONITORING SUHU DAN KONTROL KANDANG AYAM BROILER DENGAN MEMANFAATKAN DIMMER LAMPU DAN SENSOR GAS BERBASIS INTERNET OF THINGS (IOT) - Yudi Mulyanto; Yuliadi Yuliadi; Dimas Wiryatari; Putry Chaerunnisa Mudmainna (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2025)
Broiler chicken farming faces challenges in maintaining optimal air quality and cage temperature, which significantly impacts the health and productivity of the chickens. Unfavorable conditions, such as high or low temperatures and poor air quality, can cause stress in chickens, reduce their appetite, and increase the risk of disease. This study aims to design an automatic temperature and air quality monitoring system for broiler chicken cages based on the Internet of Things (IoT) using dimmer lights and gas sensors. The method used in this research is experimental, which includes hardware and software design, as well as system testing. Based on the tests, the system was proven effective in maintaining cage temperature and air quality for broiler chickens. The light intensity control successfully maintains a comfortable temperature, while the CO2 sensor accurately detects the increase in harmful gases. Additionally, energy efficiency improved due to the automatic dimmer lights. However, the system relies on a stable internet connection and requires periodic calibration of the gas sensor to ensure optimal accuracy.